Josip Procházka (1874-1956) kot "češko-slovenski" skladatelj samospevov - Weiss, Jernej (Muzikološki zbornik, 2006)
Through a comparative analysis the author of this paper attempts to determine the essential compositional-technical characteristics, as well as esthetical directions in Josip Procházka''s eleven songs published in the magazine ''Novi akordi'', written by the composer during his musical-pedagogical work in Slovenia. Wishing to determine the role and significance of the aforementioned songs in a broader creative context of the song in Slovenia, the author takes a critical view of understanding the progress as the strengthening of ''national originality'', which seems to have set significant boundaries to the editorial policy in the seemingly ''non-party'' magazine ''Novi akordi''.
Keywords: glasba; music; Novi akordi; primerjalna analiza; Procházka, Josip, 1874-1956; slovenski samospev